دراسة نظرية لتحديد عوامل الجسوءة في بلّورة المادة الفيرومغناطيسية ( الحديدية المغنطة ) (Latakia University Journal -Basic Sciences Series, 2017)
تم في هذا العمل تحديد عوامل الجسوءة ( ، ، ) في بلّورة مادة فيرومغناطيسية تدخل في حسابات ثوابت تباين المناحي ( Anisotropy) للبلورات المغناطيسية. علاوةً على ذلك, تم تحديد قيم مجالات بين متجهة تمغنط البلورة واتجاه الحقل المغناطيسي المطبق عليها , التي توافق وجود حالات التوازي ، وحالات التوازي المضاد ، وكذلك المجالات المناسبة لعملية القفز المغناطيسي بين الحالتين .This work studies the determination of stiffness factors , and in ferromagnetic crystal which enter into the calculations of anisotrophic constants of ferromagnetic crystal .However , Value intervals of C3 which coresponds to the existence of parallel states , and antiparallel states between the magnetic crystal vector and applied magnetic field vector . In addition , the suitable intervals for the magnetic jumps between two states have been found.